Towards a professional identity: Translators in the Victorian publisher’s archive - Milan, Michelle (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
This essay situates itself at the intersection of book history and translation studies, and inquires how the archive, in this instance, those of British publishers, can help us chart the development of the professional literary translator in the nineteenth century. A key period in print culture, during which many cultural, technological and social shifts occurred, the Victorian era saw the rise of the literary profession, the relevance and impact of which on literary translation can be even better understood in the light of developments in British publishing practices. Using hitherto largely untapped primary sources and uncovering a number of significant processes in the publishing history of literary translation, the discussion offers fresh insights into the production of English-language translations in nineteenth-century Britain. Drawing on the archival records of Richard Bentley’s publishing house, including translators’ correspondence and the contractual agreements that underpinned the production and publication of translations, this study inquires into what may be termed the “proto-professionalization” of literary translators in the nineteenth century.